2017
DOI: 10.1177/2325967117720171
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Pubalgia in Females: Predictive Value of MRI in Outcomes of Endoscopic Surgery

Abstract: Background:Athletic pubalgia is typically associated with male athletes participating in contact sports and less frequently with females. Endoscopic surgery may fully treat the patient with athletic pubalgia.Purpose:To perform an outcomes analysis of magnetic resonance imaging (MRI) and endoscopic surgery in female patients with athletic pubalgia.Study Design:Cohort study; Level of evidence, 3.Methods:Fifteen physically active female patients (mean age, 37 years) with athletic pubalgia were treated surgically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…59 Four articles reported bilateral repair of the posterior inguinal wall in all operated cases, independently if 1 side was asymptomatic. 45,55,57,75 Matikainen et al 45 and Paajan et al 55 justified the bilateral placement of a mesh on the posterior inguinal wall because scarring of the preperitoneal space would most likely prevent a later operation of the nonaffected side. Piozzi et al 57 and Van Meirhaeghe et al 79 argued that performing a TAPP procedure unilaterally could not fully balance and stabilize the anatomic region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…59 Four articles reported bilateral repair of the posterior inguinal wall in all operated cases, independently if 1 side was asymptomatic. 45,55,57,75 Matikainen et al 45 and Paajan et al 55 justified the bilateral placement of a mesh on the posterior inguinal wall because scarring of the preperitoneal space would most likely prevent a later operation of the nonaffected side. Piozzi et al 57 and Van Meirhaeghe et al 79 argued that performing a TAPP procedure unilaterally could not fully balance and stabilize the anatomic region.…”
Section: Discussionmentioning
confidence: 99%
“…Additional criteria in the case of comparative studies: (9) an adequate control group, (10) contemporary groups, (11) baseline equivalence of groups, (12) adequate statistical analyses. 52 5 b 0 Gill (2020) 24 Koutserimpas (2020) 37 0 1 Gerhardt (2020) 23 4 4 2 Van Meirhaeghe (2019) 79 3 3 Piozzi (2019) 57 1.5 Zoland (2018) 85 Emblom (2018) 19 1 2 2 1 9 c 0 Kajetanek (2018) 32 Roos (2018) 63 Matikainen (2017) 45 Pokorny (2017) 58 7 0 Kopelman (2016) 36 0 Santilli (2016) 67 Rossidis (2015) 65 2 Boukhris (2014) 6 5 de Queiroz (2014) 14 17 13 d Schilders (2013) 68 7 Messaoudi (2012) 46 3 Dojčinović (2012) 16 Maffulli (2012) 40 0 0 5 2 3 e Dellon (2011) 13 0 0 0 0 0 Robertson (2011) 62 1.8 0 1.8 Atkinson (2010) 2 1.5 1.5 1.5 34 Radic (2008) 60 26 Ziprin (2008) 83 Paajanen (2008) 53 12. 17 2 Kumar (2002) 38 11 Srinivasan (2002) 73 0 Irshad (2001) 30 4.5 9 4.5 Williams (2000) 82 14 f Meyers (2000) 47 1.2 0.6 Brannigan (2000) 7 Ziprin (1999) 84 Hackney (1993) 26 Malycha (1992) 41 Akermark (1992) 1 Polglase (1991) 59 1.5…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At 3 months postoperatively, patients with BME had significantly higher pain scores ( P = .03), although scores normalized at 1 and 2 years after surgery. In a follow-up study, Matikainen et al 13 performed a similar evaluation in a series of 15 female patients undergoing athletic pubalgia surgery. The authors found that female patients with BME demonstrated significantly higher preoperative pain scores than patients without BME.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment is initially conservative, with physiotherapy, rest, and anti-inflammatory drugs. On the rare occasions when the painful condition persists even after conservative treatment, surgical treatment, indicated on a case-by-case basis, may be required, including debridement of the pubic symphysis, partial pubectomy, adductor, and rectus abdominis tenotomy, or arthrodesis with use bone graft [5]. There is a multitude of differential diagnoses for pubalgia.…”
Section: Article Info Abstractmentioning
confidence: 99%